Retrieval analysis of the emission spectrum of WASP-12b: sensitivity of outcomes to prior assumptions and implications for formation history - Oreshenko,M; Lavie,B; Grimm,SL; Tsai,S-M; Malik,M; Demory,B-O; Mordasini,C; Alibert,Y; Benz,W; Quanz,SP; Trotta,R; Heng,K (Astrophysical Journal Letters, 2017)
We analyze the emission spectrum of the hot Jupiter WASP-12b using our HELIOS-R retrieval code and HELIOS-K opacity calculator. When interpreting Hubble and Spitzer data, the retrieval outcomes are found to be prior-dominated. When the prior distributions of the molecular abundances are assumed to be log-uniform, the volume mixing ratio of HCN is found to be implausibly high. A VULCAN chemical kinetics model of WASP-12b suggests that chemical equilibrium is a reasonable assumption even when atmospheric mixing is implausibly rigorous. Guided by (exo)planet formation theory, we set Gaussian priors on the elemental abundances of carbon, oxygen, and nitrogen with the Gaussian peaks being centered on the measured C/H, O/H, and N/H values of the star. By enforcing chemical equilibrium, we find substellar O/H and stellar to slightly superstellar C/H for the dayside atmosphere of WASP-12b. The superstellar carbon-to-oxygen ratio is just above unity, regardless of whether clouds are included in the retrieval analysis, consistent with Madhusudhan et al. Furthermore, whether a temperature inversion exists in the atmosphere depends on one's assumption for the Gaussian width of the priors. Our retrieved posterior distributions are consistent with the formation of WASP-12b in a solar-composition protoplanetary disk, beyond the water iceline, via gravitational instability or pebble accretion (without core erosion) and migration inward to its present orbital location via a disk-free mechanism, and are inconsistent with both in situ formation and core accretion with disk migration, as predicted by Madhusudhan et al. We predict that the interpretation of James Webb Space Telescope WASP-12b data will not be prior-dominated.